Barangay Mt. Diwata its transformation from an uninhabited hunting ground to a bustling mining community, 1983 to present - Duhaylungsod, Aaron Paul T.
The study focuses on the transformation of Barangay Mt. Diwata, popularly known as Diwalwal found in Monkayo, Compostela Valley Province from an uninhabited hunting ground of the indigenous people into a bustling mining community, with special attention to small-scale mining industry. The research is essentially qualitative, making use of Pagtatanong-tanong as the primary method of gathering data from present and former barangay officials backed up by informal contacts with key informants randomly chosen based on their position in the community. The discovery of gold in Diwalwal spread like wildfire in the neighboring towns and municipalities. It sparked a gold rush phenomena with people coming from as far as Leyte to the neighboring towns and municipalities of Monkayowho started gold panning in the Balite area. Then underground mining mostly small-scale until today's combination of large-scale and numerous-scale mining in Diwalwal. The coming of people who normally carried arms led to numerous deaths resulting to the decision to create a barangay government in the area. Moreover, the first two administrations (1984-1997) were not able to solve the problem of peace in the area. Starting 1997, during the first term of Francisco Tito, the problem of peace appeared to have improved according to several abanteros.The study also shows how the local government unit in the area, specifically the administration of Tito, responded the problems faced by the people as a result of the various forces acting on each other in Barangay Diwalwal. Problems continue to exist in the area foremost of which are: the peace and order condition, albiet in the reduced form today; ecological concerns; and the entry of foreign mining companies in their community. Strengthened by their experiences since 1983, the local officials and constituents are confident that, together, they would be able to face the challenges posed by the mining activities within the barangay. This study contributes to the discourse on community formation and local governance. It also provides first hand information on the current issues and concerns that is faced by Barangay Diwalwal. The result of this study provide some insights and information on the operation of the mining industry in the country.